Efektivitas Program Pendidikan Keluarga tentang 'Bahasa Cinta' terhadap Peningkatan Kualitas Komunikasi Pasangan Suami Istri di Paroki Santo Mikhael Kota Baru, Kabupaten Ende - Mathilde Mitha; Fransiskus Z. M.Deidhae; Maria Yulita C. Age; Damianus Dionisius Nuwa (MASALIQ, 2026)
A lack of open communication in married life can lead to misunderstandings and conflicts because some couples assume that expressions of affection are only necessary during the stages of acquaintance and courtship. This condition indicates the importance of family education on love languages as an effort to improve the quality of communication between married couples in Catholic families. This study aims to analyze the effectiveness of a family education program on love languages in improving the quality of communication between married couples at Santo Mikhael Kotabaru Parish, Ende Regency. The study employed a quantitative method with a pre-experimental approach using a one-group pretest–posttest design. The program was conducted on October 8, 2025, at the Santo Mikhael Kotabaru Parish Hall and involved married couples who had been married for five to ten years. The findings indicate that the family education program on love languages was effective in improving participants’ understanding of their partners’ emotional needs and the importance of communication within the family. The program also encouraged changes in attitudes and behavior and increased couples’ awareness of the role of communication in maintaining marital harmony. This study concludes that understanding and applying love languages can help couples maintain emotional closeness, develop mutual understanding, and resolve problems in their relationships. These findings provide practical implications for the development of family education programs within parish communities that focus on strengthening communication, harmony, and the resilience of marital relationships.